Halliday’s Language Metafunction on Queen’s “Bohemian Rhapsody” - Metekohy Marschall Eirence (Prologue: Journal on Language and Literature, 2021)
This paper discusses the use of Language Metafunction in the song “Bohemian Rhapsody”. This research aims to identify the ideology of the song as portrayed through the words and actions of the protagonist in this song. This research focused on every single word in the lyric. The study used qualitative and descriptive methods. The data collection was obtained from genius.com. The data was analyzed by using Language Metafunction theory by Halliday’s Ideational, Interpersonal, and Textual Meaning. The results of the research show that three dominant processes of language can be found are Relational Process, Material Process, and Mental Process; with the last mentioned being the dominant one. Also, by analyzing the lyric, it can be concluded that the ideology of the song is the songwriter believes that all things that happened in the past are in the past.